Dimensional tolerances for additive manufacturing: Experimental investigation for Fused Deposition Modeling - Lieneke, Tobias; Denzer, Vera; Adam, Guido; Zimmer, Detmar (CAT 2016)
Additive manufacturing creates parts in layers without using formative tools. Compared to established manufacturing processes, additive manufacturing offers many advantages. However, only a few research institutions and technology-leading companies use additive manufacturing for end-use part production because relevant challenges have not been sufficiently researched yet. Missing restrictions become apparent in the available geometrical accuracy. The objective of this investigation was the experimental determination of dimensional tolerances using standard parameters. To this end, a methodical procedure was set up. Based on experimentally determined deviations, dimensional tolerances were derived.

Effizienzorientierte Optimierung der Baustruktur von MMDS-Sammelgetrieben - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Intelligent Operating Strategy for an Internal Rubber Mixer's Multi-Motor Drive System Based on Artificial Neural Network - Strop, Malte; Zimmer, Detmar (IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA))

Örtlich konzentrierte Mehrmotorenantriebssysteme - Ein Lösungsansatz für ganzheitlich modulare Antriebssysteme - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Optimierung von Planetengetriebemotoren - Einfluss des Übersetzungsverhältnisses auf das Kosten-, Gewichts-, Verlust-, Dynamik- und Zuverlässigkeitsverhalten von Planetengetriebemotoren - Kücükyavuz, Ali Kemal

Beitrag zur Reduzierung der Verluste von fluidabdichtenden Wellendichtsystemen - Nolte, Karsten

Verbundprojekt Energieeffiziente Federkraftbremse: Abschlussbericht. Berichtszeitraum: 01.05.2012 - 31.03.2016 - Schadomsky, Magnus Hubert; Zimmer, Detmar; Kriegel, Nils-Peter; Neumann, Christoph; Küter, Winfried; Menzel, Eckard

A Holistic and Adaptive Approach for Automated Prototyping of Image Processing Functionality - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 21st IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))
Image Processing is fundamental for any camera-based vision system. In order to automate the prototyping process of image processing solutions to some extend, we propose a holistic, adaptive approach that comprises concepts for specification, composition, recommendation, execution, and rating of image processing functionality. The fundamental idea is to realize image processing applications according to Service-oriented Computing design principles. That is, distinct image processing functionality is encapsulated in terms of stateless services. Services are then used as building blocks for more complex image processing functionality. To automatically compose complex image processing functionality, our proposed approach incorporates a flexible, Artificial Intelligence planning-based forward search algorithm. Decision-making between alternative composition steps is supported by a learning recommendation system, which keeps track of valid composition steps by automatically constructing a composition grammar. In addition, it adapts to solutions of high quality by means of feedback-based Reinforcement Learning techniques. A concrete use case serves as proof of concept and demonstrates the feasibility of our holistic, adaptive approach.

Do talented women shy away from competition? - Hoyer, Britta; van Huizen, Tomas; Keijzer, Linda; Rezai Khavas, Tahere; Rosenkranz, Stephanie
We study the willingness to compete in a cognitive task among an entire cohort of fresh man business and economics students. Combining data from a lab-in-thefield experiment with university admissions data, we trace the gender gap in competitiveness at different levels of high school performance. Our results confirm that, on average, men choose to compete more often. The gender gap disappears, however, among students with above average high school performance. Female high school top performers are equally competitive as their male counterparts. In fact, the overall gender gap is entirely driven by the group of female high school underperformers who shied away from competition, even when they performed well in our task. Overall, our findings suggest that high school grades are more than just a signal of cognitive abilities, because they seem to influence the receivers selfperception of his or her performance in a competitive environment involved in later on in life.

A Formal Approach to Error Localization and Correction in Service Compositions - Krämer, Julia; Wehrheim, Heike (Proceedings of the 1st International Workshop on Formal to Practical Software Verification and Composition (VeryComp 2016))
Error detection, localization and correction are time-intensive tasks in software development, but crucial to deliver functionally correct products. Thus, automated approaches to these tasks have been intensively studied for standard software systems. For model-based software systems, the situation is different. While error detection is still well-studied, error localization and correction is a less-studied domain. In this paper, we examine error localization and correction for models of service compositions. Based on formal definitions of error and correction in this context, we show that the classical approach of error localization and correction, i.e. first determining a set of suspicious statements and then proposing changes to these statements, is ineffective in our context. In fact, it lessens the chance to succeed in finding a correction at all.In this paper, we introduce correction proposal as a novel approach on error correction in service compositions integrating error localization and correction in one combined step. In addition, we provide an algorithm to compute such correction proposals automatically.